Oral Contraceptive Use Dampens Physiological Adaptations to Sprint Interval Training. - Schaumberg, M.; Jenkins, D.; Janse de Jonge, X.; Emmerton, Lynne; Skinner, T. (Lippincott Williams & Wilkins, 2016)
PURPOSE: Oral contraceptive (OC) use reduces peak aerobic capacity (VO2peak), however, whether it also influences adaptations to training has yet to be determined. This study aimed to examine the influence of OC use on peak performance [peak power output (PPO)] and physiological adaptations [VO2peak and peak cardiac output (Qpeak)] following sprint interval training (SIT) in recreationally-active women. METHODS: Women taking an OC (n=25) or experiencing natural regular menstrual cycles (MC; n=16) completed an incremental exercise test to assess VO2peak, PPO, and Qpeak before, immediately after, and four weeks following 12 sessions of SIT. The SIT consisted of 10, one-minute efforts at 100-120% PPO in a 1:2 work:rest ratio. RESULTS: Though VO2peak increased in both groups following SIT (both p<0.001), the MC group showed greater improvement (OC +8.5%; MC +13.0%; p=0.010). Similarly, Qpeak increased in both groups, with greater improvement in the MC group (OC +4.0%; MC +16.1%; p=0.013). PPO increased in both groups (OC +13.1%; MC +13.8%; NS). All parameters decreased four weeks after SIT cessation, but remained elevated from pre-training levels; the OC group showed more sustained training effects in VO2peak (OC -4.0%; MC -7.7%; p=0.010). CONCLUSION: SIT improved peak exercise responses in recreationally-active women. However, OC use dampened VO2peak and Qpeak adaptation. A follow-up period indicated that OC users had spared VO2peak adaptations, suggesting that OC use may influence the time course of physiological training adaptations. Therefore, OC use should be verified, controlled for, and considered when interpreting physiological adaptations to exercise training in women.